2022
DOI: 10.3390/s22166060
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress in Distributed Acoustic Sensing Techniques

Abstract: Distributed acoustic sensing techniques based on Rayleigh scattering have been widely used in many applications due to their unique advantages, such as long-distance detection, high spatial resolution, and wide sensing bandwidth. In this paper, we provide a review of the recent advancements in distributed acoustic sensing techniques. The research progress and operation principles are systematically reviewed. The pivotal technologies and solutions applied to distributed acoustic sensing are introduced in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 94 publications
1
23
0
Order By: Relevance
“…Even though current commercial DAS systems allow a thorough monitoring along a maximum distance of 50 kilometers, recent studies have shown that persistent monitoring could be enabled up to a hundred kilometers. The most common DAS technologies are based on phase sensitive Optical Time Domain Reflectometer (φ-OTDR) and coherent OTDR (C-OTDR) [40]. A DAS interrogator unit generates a series of laser pulses, sends them through the optical fiber cable, and collects the backscattering of the light along the length of the fiber.…”
Section: Distributed Acoustic Sensingmentioning
confidence: 99%
“…Even though current commercial DAS systems allow a thorough monitoring along a maximum distance of 50 kilometers, recent studies have shown that persistent monitoring could be enabled up to a hundred kilometers. The most common DAS technologies are based on phase sensitive Optical Time Domain Reflectometer (φ-OTDR) and coherent OTDR (C-OTDR) [40]. A DAS interrogator unit generates a series of laser pulses, sends them through the optical fiber cable, and collects the backscattering of the light along the length of the fiber.…”
Section: Distributed Acoustic Sensingmentioning
confidence: 99%
“…In recent years, efforts have been devoted to transform fiber-optic cables into dense arrays of sensors with technologies that leverage various back-scattering effects of light pulses [18,19]. Among these, Distributed Acoustic Sensing (DAS) has gained wide interest thanks to its ability to monitor seismo-acoustic signals and dynamic strain with high sensitivity [20,21], making it suitable for a wide range of geophysical monitoring applications [22,23,24,25,26,27,28,29,30,31]. Specifically, DAS systems rely on the analysis of the Rayleigh back-scattering spectrum of light.…”
Section: Das Thermometrymentioning
confidence: 99%
“…At the same time, diverse techniques exist to preserve an optimal DAS repeatability at long distances (e.g. Shang et al, 2022).…”
Section: Lf-das and Alternative Dfos Approachesmentioning
confidence: 99%